1996
DOI: 10.1097/00004836-199601000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Splenomegaly in Portal Hypertension

Abstract: Splenomegaly is obvious in portal hypertension, but controversy still exists over the relationship between splenic size or size of esophageal varices. Previous methods to assess spleen size are less accurate than ultrasonic estimation of spleen size by splenic volumetric index (SVI). In a prospective study, we evaluated 101 consecutive patients with portal hypertension for spleen size measured ultrasonically by SVI, presence and size of esophageal varices, and etiology of portal hypertension. A total of 219 ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The splenomegaly developing in the context of liver cirrhosis is commonly ascribed to blood congestion, but older studies demonstrated that it cannot be considered only as a consequence of increased portal pressure and augmented resistance to splenic vein outflow 21 . Surprisingly, no relationship could be found between the spleen size and the degree of esophageal varices 22 . Multiple studies demonstrated pooling of blood in the red pulp, intraparenchymal arterial aneurysms, 23 and other multiple histopathologic changes, which evolve towards diffuse fibrosis of the spleen, 24 more likely because of endothelin overexpression and changes in the balance of endothelin receptors 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The splenomegaly developing in the context of liver cirrhosis is commonly ascribed to blood congestion, but older studies demonstrated that it cannot be considered only as a consequence of increased portal pressure and augmented resistance to splenic vein outflow 21 . Surprisingly, no relationship could be found between the spleen size and the degree of esophageal varices 22 . Multiple studies demonstrated pooling of blood in the red pulp, intraparenchymal arterial aneurysms, 23 and other multiple histopathologic changes, which evolve towards diffuse fibrosis of the spleen, 24 more likely because of endothelin overexpression and changes in the balance of endothelin receptors 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The spleen has a crucial role in pathogenesis and maintenance of portal hypertension [16,17] . In portal hypertension, the anatomic changes of the spleen (pulp hyperplasia, congestion and fibrosis) and specific vascularization affect the hemodynamics of the splenic circulation [18] .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, no correlation has been found between spleen size and portal pressure (3,4) and con icting data have been reported about the correlation between spleen size and the size of oesophageal varices (5,6). However, in Child-Pugh A stage cirrhosis, splenomegaly has been shown to be an independent predictor of survival (7).…”
mentioning
confidence: 99%